Analysis of morbidity and health care usage of patients with suspected thyroid disorders - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Kühlein, Thomas; Hueber, Susann (Preventing Overdiagnosis Congress 2019, 2019)
Objectives (150 words) In many countries the incidence of thyroid cancer increased in the last years, while thyroid cancer mortality remained stable. This is seen as an indicator for overdiagnosis. Furthermore, many surgically removed thyroid nodules turn out to be benign, especially in Germany. Germany has a highly fragmented health care system with easy access to diagnostic imaging even at the level of general practice. Most thyroid nodules are detected using sonography early in the work-up of suspected thyroid disorders, which might trigger control loops and invasive treatment. Thus, the objective of this study is to systematically analyze whether the early use of sonography in the work-up of suspected thyroid disease might lead in a cascade effect from overdiagnosis to overtreatment. The following research question will be answered: What effects does the early use of sonography in the diagnostic process of suspected thyroid disorders have on morbidity, health care utilization and costs? Method (150 words) To answer this research question a retrospective cohort-study design comparing two propensity-matched groups was chosen. Claims data of patients with statutory health insurance held by the Bavarian Association of Statutory Health Insurance Physicians were used. Early use of sonography was defined as having an initial TSH test followed by a sonography within 28 days. Patients having received a TSH test in 2012 were included and allocated to one of the two following groups: Group 1: TSH test followed by sonography of the thyroid within 28 days. Group 2: TSH test without sonography of the thyroid within 28 days. The two groups were matched for sociodemographic characteristics, morbidity, and reason for encounter using propensity score matching. The two groups are currently compared in terms of morbidity, health care utilization and costs. Results (150 words) After propensity score matching, the sample consisted of 68,862 patients in each group. Data analysis is not completed yet. The results will be available for presentation until the conference. Conclusions (150 words) Early use of sonography in the work-up of suspected thyroid disorders might trigger a cascade of overdiagnosis and overtreatment. By systematically analyzing clinical pathways of patients with suspected thyroid disorders and the resulting medical and economic consequences, we hope to contribute to the identification and reduction of overdiagnosis and overtreatment concerning thyroid disorders. The project is embedded in the PRevention of Overdiagnosis in PRImary CARE (PRO PRICARE) research network funded by the German Federal Ministry of Research and Education. </